INDE METADATA CONFORMITY INDICATOR - Gottardo, Taís; Barbosa, Ivanildo (Boletim de Ciências Geodésicas, 2019)
Metadata represents a set of descriptive information about the data, which aims at facilitating the search, access and use of data. The metadata standards specify the minimum set of elements to be informed and the file structure to ensure interoperability among catalogs. The present work aims at analyzing the adherence of the metadata published in the Brazilian Spatial Data Infrastructure (SDI) repository to the MGB Profile (in Portuguese, Perfil de Metadados Geoespaciais do Brasil) through a conformity indicator. Conformity was evaluated for over 30,000 metadata inserted in the INDE catalog (in Portuguese, Infraestrutura Nacional de Dados Espaciais), in June 2018, considering the set of mandatory and conditional elements of the summarized MGB Profile. These elements were collected from a harvester elaborated by the authors capable of scanning all the metadata of the repository and returning the fields organized into a CSV file. After analysis, it was found that only 28% of metadata conforms to the summarized MGB Profile. The low conformity rate suggests the limited understanding of the standards recommended, regarding both the minimum elements to be informed about each product and the structuration of the information in XML.